The impact of modified modular health teaching on enhancing the client's cognitive level on diabetes mellitus and compliance to diet and medication regimen - Maghuyop, Samuel; Torres, Melanie Joy; Ampongan, Antonnette Jennifer; Benemerito, Rommel; Cabela, Joy Caromel; Francisco, Jr., Francisco; Oropesa, Ruth; Pagulayan, Divina Gracia; Patawaran, Kristine Grace; Regala, Trina Fe; Verzo, Cristina
The self-care capabilities of a diabetes mellitus patient is vital in the effective control of the illness. This is usually developed according to the knowledge and training imparted by health personnel to the patient. Thus this study was done to determine the following: (1) the presence of a relationship between health teaching and the patient’s cognitive level. and compliance to diet and medication regimen; (2) the effect of health teaching on the patient’s cognition on illness and its management and his or her’ actual compliance to diet and medication regimen; (3) the factors affecting an individual's improvement of cognitive level and compliance to diet and medication regimen.